2007
DOI: 10.1264/jsme2.22.59
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Nitrogen-fixing Activity of Enterobacteriaceae Strains Isolated from Sago Palm (Metroxylon sagu) by Microbial Interaction with Non-nitrogen Fixers

Abstract: This study was done to determine microbial interactions between nitrogen-fixing bacteria (NFB) and different indigenous bacteria, both of which were isolated from the same samples of sago palm. Co-culture of NFB and indigenous bacteria, isolated using nutrient agar medium, into a nitrogen-free Rennie medium showed significantly higher nitrogen-fixing activity (NFA) than single inoculations of NFB did in almost all combinations. A reduced oxygen status also enhanced the NFA of NFB. All NFB preferred simple suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
1
26
0
1
Order By: Relevance
“…These invasive endophytes may be useful as more stable vehicles to deliver genes into host plant cells. In addition, it has been reported that starch-degrading strains stimulate the activities of nitrogen-fixing bacteria, both of which were isolated from the same samples of sago palm (41). The starch-degrading endophytes detected in rice plants may have similar functions.…”
Section: Resultsmentioning
confidence: 96%
“…These invasive endophytes may be useful as more stable vehicles to deliver genes into host plant cells. In addition, it has been reported that starch-degrading strains stimulate the activities of nitrogen-fixing bacteria, both of which were isolated from the same samples of sago palm (41). The starch-degrading endophytes detected in rice plants may have similar functions.…”
Section: Resultsmentioning
confidence: 96%
“…Diazotrophic bacteria may accumulate, depending on their environment, and their role in the acquisition of N for M. malabathricum may also differ among soil types. Furthermore, the co-culture of diazotrophic bacteria and non-diazotrophic bacteria was reported to enhance or induce nitrogen-fixing activity (21,29). So we need to pay attention to microbial interactions between diazotrophic bacteria and other indigenous bacteria in the rhizosphere of M. malabathricum.…”
Section: Resultsmentioning
confidence: 99%
“…Microbes like bacteria and fungi which live inside healthy plant tissues without causing apparent symptoms, known as endophytes 33) are also known to form mutually beneficial relationships with their hosts 23) . Being mutualists, these microbial populations are known to be beneficial to host plants by enhancing the absorption of soil nutrients such as phosphorus and other inorganic elements, nitrogen-fixing efficiency 38,43) and plant growth with the production of hormones like auxins, abscisins, ethylene, gibberellins, and kinetins 20,29) . They provide protection to their hosts against insect pests 27) , herbivores 11) , and microbial pathogens 39,42,44) .…”
mentioning
confidence: 99%